Análise de critérios de seleção de materiais e processos para interiores de aeronaves executivas incorporando aspectos de sustentabilidade - Santos, Celise Villa dos (Universidade Federal de São Carlos, 2015)
Materials and processes used to manufacture executive aircraft interiors play an important role in aesthetic and competitive product differentiation, in a scenario where there is growing competition and pressures for more sustainable products. It has been observed that the selection of these materials and processes, in the early stages of product development, has introduced limited measures to reduce costs and environmental improvements in manufacturing, which is reflected in the scientific literature available. This research addresses procedures for materials and processes selection including these factors, as well as other customer and aeronautical design requirements, which requires specialized information and methods of analysis established for this approach of priorities. The aim was to evaluate the current materials and processes and identify new opportunities, looking for a strategy to improve the selection methodology, as a contribution to greater integration design - materials - processes. The main analytical tool used was Value Stream Mapping, associating concepts of lean manufacturing, design for manufacturing and assembly, ecodesign and product lifecycle. Mapping applied to case studies involving an item of furniture was suitable to draw closer environmental requirements and manufacturing prospecting activities, as well as selecting materials and processes. The research also explored solutions filed on patents and knowledge from other industrial sectors which were in line with the opportunities. One example is biopolymer solid panels reinforced with natural fibres, as substitutes for structural materials produced from non-renewable and toxic sources, which require adding resins to reinforce and close the honeycomb core. There was synergy between the possible solutions aimed at improving the economic performance and environmental sustainability of the product, such as ultraviolet radiation curable resins to finish the panels.
ANALYSIS OF MATERIALS AND PROCESSES SELECTION CRITERIA FOR EXECUTIVE AIRCRAFT INTERIORS INCLUDING SUSTAINABILITY ISSUES
Keywords: Seleção de materiais; Seleção de processos; Interior de aeronaves; Sustentabilidade; CIENCIAS EXATAS E DA TERRA